Fucoxanthin Inhibits the Proliferation of ABCC2-Over Expressing Cisplatin-Resistance Ovarian Cancer Cells via Inducing Apoptosis - Fatemeh Valinezhad Sani; Safa Kamalian; Hakimeh Abdi; Shiva Ghofrani; Arad Boustan; Fatemeh Mosaffa (Tabriz University of Medical Sciences, 2023)
Background: The development of multidrug resistance (MDR) is a major barrier to achieving effective chemotherapy in cancer. Studies have shown that epithelial ovarian cancer initially responds to platinum-based therapy, however, the recurrent type is often resistant to treatment and is associated with high mortality. Fucoxanthin, a natural component found in marine algae, possesses various pharmacologic properties. This study evaluated the cytotoxicity and resistance reversal activity of fucoxanthin on multidrug resistance-associated protein 2 (MRP2)- overexpressing, cisplatin-resistant ovarian cancer cells (A2780RCIS) and their parental cells (A2780). Methods: Cell viability was evaluated in the presence of different concentrations of fucoxanthin or cisplatin or fucoxanthin/cisplatin combination using the MTT assay. Propidium iodide staining and subG1 analysis were used to evaluate fucoxanthin potential for cell cycle modification and apoptosis induction in cancer cell lines. Results: The results showed that fucoxanthin was able to cause similar toxicity in both cell lines via apoptosis induction. Co-treatment of cells with cisplatin (3.125 to 100 µM) and nontoxic concentrations of fucoxanthin (1 and 2.5 µM) did not reverse resistance to cisplatin in A2780RCIS cells. Conclusion: Although fucoxanthin was not able to modify cisplatin resistance in ovarian cancer cells, it was equally effective in inducing apoptosis and death in both A2780 and A2780RCIS cells, indicating it is not an MRP2 substrate.